Editorial - Sarapura Sarapura, Mercedes Milagro (2023)
If one thinks that the world is a labyrinth, affirms Borges, it is because perhaps, then, it has a center, and that would mean that we are saved, but there is no certainty about that, reflects the author, and rather, it could be let it be chaos and then we would be lost, the truth is that the scenario of globalized society rises above that uncertainty, which I wish was a labyrinth, but there is no doubt, of arduous and multiple subterfuges that make their way into a reality that when it barely begins to be concrete, it ends up being virtual or vice versa: the surreptitious passages of both dimensions, full of information and experiences, converge in the same consciousness, in the same mind and in the same feeling; an experience from which no one can escape because, among other things, it is about the post-truth era.